Physicomechanical characteristics and mix proportions of a new transparent cemented soil: similar material tests and ANOVA/ANOR analyses - He, Shengya; Li, Hengyi; Ye, Liang; Huang, He; Peng, Wei; Xie, Peng; Wang, Zhijia; Zhang, Youliang; Lin, Shu; Wen, Haijia; Fan, Zhanfeng; Duan, Huchen (Frontiers in Materials, 2025)
During tunnel excavation in a soft soil stratum, a transparent model test can present the whole failure process, and a similar transparent material with stable physical and mechanical properties is essential for obtaining valid experimental results. Therefore, a new type of similar transparent material was developed in which fused quartz sand served as the coarse aggregate, nanoscale hydrophobic fumed silica powder acted as the binder, and a mixture of n-dodecane and 15# white oil was used as the pore fluid. The key parameters of the developed similar transparent material, including unit weight, internal friction angle, cohesion, and compression modulus, were evaluated. Furthermore, the consistency between the similar transparent material and natural soft soil was verified in three aspects, namely, physical properties, compressive strength characteristics, and shear properties. Finally, appropriate adjustment measures were proposed based on the results of the analysis of variance (ANOVA) and the analysis of range (ANOR) to meet the similarity requirements of parameters under different engineering conditions.